Isa Al-Masih Putera Maryam: Suatu Taakulan - Mohd. Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 1996)
The word al-Masih is a theological term used in certain words i.e:- al-Masih al-Dajjal and Masih al-Mar’ah which have their own meaning. However the word al-Masih is always associated to Isa which is known as ’Isa al-Masih or al-Masih son of Maryam. Thus, the concept of al-Masih and why it is associated to Isa is not known. Therefore, this article attempts to elaborate comprehensively the word al-Masih in various taakulan based on theories which are already exist.